Understanding the efficacy of N, N-dimethylformamide and oxalyl chloride combination as chemoselective O-formylating agent: An unified experimental and theoretical study. Issue 8 (17th April 2016) - Batuta, Shaikh; Ali, Md. Ashif; Chatterjee, Anirban; Alam, Md. Niharul; Das, Sreeparna; Mandal, Debabrata; Begum, Naznin Ara
ABSTRACT: We have developed a simple but efficient synthetic protocol for the O- formylation of a wide range of aromatic hydroxyl/phenolic substrates using an N, N -dimethylformamide (DMF) and oxalyl chloride [(COCl)2 ] combination in dichloromethane (DCM) as solvent at ambient temperature. The DMF/(COCl)2 combination was found to be highly chemoselective for the aromatic/phenolic hydroxyl group over aliphatic hydroxyl or aromatic amine/thiol groups. This chemoselectivity of DMF/(COCl)2 combination towards O- formylation of aromatic alcohols was explained on the basis of outcomes of both experimental and density functional theory–based theoretical studies. GRAPHICAL ABSTRACT: